Vitiligo: A Review of its Aspects and Treatment Modalities - Sureshkumar, Dr. Raman (Asian Journal of Pharmaceutics (AJP), 2018)
Vitiligo is a depigmentation disorder which occurs irrespective of parts of the body. Loss of melanin a pigment present in the body which occurs due to various factors including stress factors, hormonal, chemical factors, and genetics have been associated with the cause of the disorder. Many treatment methods are available for vitiligo, but no treatment produces complete repigmentation. Appearance of widespread patches on the body of the patients causes psychological distress. Most of the treatment methods utilize ultraviolet (UV) rays combinational strategy. Increased exposure of UV rays causes many side effects which include itching, burning sensation and xerosis.. It is not the affected area alone is exposed also the adjoining parts. The use of herbal medicines and other combination treatment can help to subside the progression of disease. In this review, we made an attempt to study the different methods of treatment, its mechanism and alternative methods for vitiligo.